دور استراتيجية النمو في تعزيز تنافسية المؤسسة (مؤسسة المراعي نموذجا) - سعيدة, عبد الكريم; صخر, أحمد; جديدي, روضة (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الورقة البحثية الي محاولة تحديد العلاقة بين استراتيجية النمو و بين تنافسية المؤسسة وذلك من خلال طرح الاشكالية التالية ماهو دور استراتيجية النمو في تعزيز تنافسية المؤسسة ومن اجل الاجابة على الاشكالية المطروحة قمنا بالاستعانة بوثائق المؤسسة المتمثلة في التقرير المالية السنوية وتحليلها باستخدام برنامج EXEL وقد توصلت الدراسة الى ان استراتيجية الاستحواذ لها اثر ايجابي في تحقيق نمو المؤسسة. Abstract: This research paper aims to try to define the relationship between growth strategy and enterprise competitiveness by presenting the following problem What is the role of growth strategy on enhancing enterprise competitiveness and in order to answer the problem posed using the documents of the institution represented in the annual financial report and its analysis using the EXEL program has reached The study indicates that the acquisition strategy has a positive impact on achieving the growth of the organization
The role of growth strategy on enhancing enterprise competitiveness (Almarai Institution as )as a Model)
مقال
Keywords: النمو ، التنافسية، الاندماج و الحيازة، الاستحواذ، الحصة السوقية; Growth, competitiveness, merger and acquisition, acquisition, market share